Rekonstruksi Peraturan Daerah Diskriminatif: Suatu Kajian Yuridis Pada Kasus Jilbabisasi Di Aceh - Maichle Delpiero; Karina Widyadhari Argyapalastri Aryanto Putri; Muhammad Labib Wajdi; Jessica Valencia; Ratih Mulia Fazriati (CV. ULIL ALBAB CORP, 2022)
The phenomenon of (hijab)ization in educational institutions in Aceh had become an issue among the government and society nowdays. The case began with the practice of raids on students who did not wear Islamic attire as stipulated in Article 13 of Aceh Qanun Number 11 of 2002 concerning the Implementation of Islamic Shari'a in the Field of Aqidah, Worship and Islamic Syi'ar. The reason is, students who are non-Muslims are also subject to raids on the basis of violating the obligation to dress Islamically. With the background of this case, the writer formulates two main problems, namely, first, whether the sharia-based content in Aceh Qanun Number 11 of 2002 is contrary to the state constitution. Second, how is the process of reconstructing the content of sharia-based regional regulations in the case of (hijab)ization in Aceh. This research uses normative juridical research which is sourced from secondary data including primary legal materials in the form of legislation and secondary legal materials in the form of books, journals, and relevant references. This study finds that Article 13 of Aceh Qanun Number 11 of 2002 concerning the Implementation of Islamic Shari'a in the Field of Aqidah, Worship, and Syi'ar Islam is unconstitutional and a reconstruction effort is needed by adjusting to regulations at the top level in order to realize the fulfillment of constitutional rights in the 1945 Constitution.